Cellular - Papadaki, M. (IEEE Engineering in medicine and biology magazine)
Promising approaches to regenerate corneas, heart valves, and thymus have been presented in recent press releases. These are described here: Tsai et al. in The New England Journal of Medicine presented a promising technology to reconstruct damaged ocular surfaces; CryoLife wants to conduct clinical trials for the use of its Synergaft tissue-engineered replacement heart valves in heart reconstruction surgery for children requiring replacement of the pulmonary heart valve; NIST Researchers at Cytomatrix and Massachusetts General Hospital have generated an "artificial thymus" that can efficiently generate large quantities of a wide range of human T-lymphocyte cells, a key element of the body's immune system.